Regulation of Withdrawals in Individual Account Systems - Walliser, Jan (IMF Working Papers; Working Paper, 1999)
Funded mandatory pension systems based on individual accounts are spreading around the world. With the maturation of these systems, regulating the withdrawal of retirement savings will become increasingly important. Government regulation of withdrawals should mandate the purchase of inflation-indexed life annuities exceeding income available from government welfare programs for the retiree and potential survivors. Proper functioning of insurance markets does not, however, require annuitizing the entire account balance. Instead, more flexibility for the choice of withdrawals could be permitted for any remaining funds, helping to tailor income streams to individual needs and living arrangements.